Estimation of the prevalence of substance use by wastewater-based epidemiology study in four cities of Guangdong, China - Wei Wang; Dan Wang; Li Liu; Cunxi Qiu; Junyi Fan; Yuhan Jin (PLoS ONE, 2025)
Introduction The widespread use of illegal drugs and their associated problems have emerged as a significant public health concern. This study was conducted to estimate the consumption and prevalence of substance use in selected cities of Guangdong Province through wastewater-based epidemiology. Methods We collected influent wastewater samples from 67 wastewater treatment plants across four cities of Guangdong from May 2023 to April 2024. The samples were analyzed using solid-phase extraction and liquid chromatography-mass spectrometry to identify 10 commonly used drugs and their metabolites in wastewater. By measuring the concentrations of these drug biomarkers, we estimated drug consumption, prevalence, and the number of individuals abusing drugs. Results Our analysis revealed the presence of six out of ten monitored illicit drugs in the samples from the four cities. Methamphetamine emerged as the most consumed drug in Guangdong Province, with consumption ranging from 65 to 223 mg/1000 inh/d. This was followed by heroin (19–55 mg/1000 inh/d), codeine (7–20 mg/1000 inh/d) and ketamine (1–13 mg/1000 inh/d). The prevalence rates of methamphetamine, heroin, and ketamine across four cities of Guangdong Province were found to be 0.149%-0.411%, 0.003%-0.019%, and 0.003%-0.196%, respectively. Notably, between 2023 and 2024, the prevalence of heroin displayed a notable downward trend, while the prevalence of both methamphetamine and ketamine exhibited a marked upward trend. Discussion Our comprehensive analysis of the substance use situation in these cities indicated that methamphetamine, heroin, and ketamine were the most used substances. Cocaine was detected in only two WWTPs whereas MDMA was found in two separate plants. The cities with the highest and lowest prevalence rates of these three drugs were variant. This study provides valuable data that can support real-time monitoring of regional substance use situations, aiding in developing effective intervention strategies.